2010
DOI: 10.1210/jc.2009-2795
|View full text |Cite
|
Sign up to set email alerts
|

BRAFV600E Mutation Analysis in Fine-Needle Aspiration Cytology Specimens for Evaluation of Thyroid Nodule: A Large Series in aBRAFV600E-Prevalent Population

Abstract: Molecular testing for the BRAFV600E mutation in FNA thyroid nodule specimens increases diagnostic value when applied in a BRAFV600E mutation-prevalent population. However, when using this potentially powerful technique, we must consider both its strengths and its weaknesses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
144
2
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 151 publications
(160 citation statements)
references
References 27 publications
12
144
2
2
Order By: Relevance
“…As many as 181 (18.3%) FNACC results were in group 6, and postoperatively on histopathology in 180 cases of PTC [162 BRAF V600E (+), and among BRAF V600E (-): 18-PTC and in one-MTC] were revealed. This is probably the reason for such high sensitivity: 82.5% obtained in this study [20]. A high (75%) sensitivity was also obtained in detection of BRAF V600E mutation in the study by Jo et (+) mutation was present in 22 patients with cytological group 6 (malignant), in 7 indeterminate nodules, and in 1 from the non diagnostic cytology group [21].…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…As many as 181 (18.3%) FNACC results were in group 6, and postoperatively on histopathology in 180 cases of PTC [162 BRAF V600E (+), and among BRAF V600E (-): 18-PTC and in one-MTC] were revealed. This is probably the reason for such high sensitivity: 82.5% obtained in this study [20]. A high (75%) sensitivity was also obtained in detection of BRAF V600E mutation in the study by Jo et (+) mutation was present in 22 patients with cytological group 6 (malignant), in 7 indeterminate nodules, and in 1 from the non diagnostic cytology group [21].…”
Section: Discussionsupporting
confidence: 66%
“…Sensitivity markers of BRAF V600E mutation in material obtained from FNAB in the diagnosis of TC in different studies range from about 32% (Cohen [19]) to 82 % (Kim [20]). …”
Section: Discussionmentioning
confidence: 99%
“…Zatelli et al (2009) found sensitivity of 64% and Sapio et al (2007) found sensitivity of 37.5% from specimens of inconclusive cytology. A study from Kim et al (2010), in Korea where the prevalence of BRAF mutation is high on their population revealed a sensitivity of 82.5% and a higher value until 98.5% if BRAF mutation was combined with cytology examination.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies reported that the BRAF mutation is a highly accurate marker of malignancy for thyroid nodules sampled by FNAB [205][206][207][208][209]. However, the most frequent diagnostic problems in FNAB samples are indeterminate follicular tumors and suspicion of malignancy according to the Bethesda system.…”
Section: Molecular Targets In Histopathological Diagnosis and Classifmentioning
confidence: 99%